Ghost cell odontogenic cyst : A rare case with literature review - Shivakumar, B.N.; Reddy, Santhosh; Nayak, Barakha; Rathore, Nehal (Asian Journal of Medical Sciences, 2015)
Gorlin in 1962 described calcifying odontogenic cyst (COC) for the first time as a separate entity. It is an odontogenic cyst with notable presence of histopathological features which contains a cystic lining demonstrating “Ghost” cells with a propensity to calcify. COC shows diversity of variants according to its clinical, histopathological & radiological characteristics. A case of calcifying odontogenic cyst is reported with its review of literature. DOI: http://dx.doi.org/10.3126/ajms.v6i4.11586 Asian Journal of Medical Sciences Vol.6(4) 2015 83-86